Analisis Kebutuhan Bahan Ajar Muatan Lokal Sejarah dan Budaya Kabupaten Bone di Sekolah Dasar - Tati, Andi Dewi Riang (ISTORIA : Jurnal Pendidikan dan Ilmu Sejarah, 2016)
This study aims to describe the level of local content requirement of teaching materials and cultural history Bone Elementary School. The method used is the Research and Development which is used to produce models of teaching materials developed are teaching materials local content subjects sejarh and culture for elementary school students based on the history and culture Bone. This study are preliminary or prasurvei, namely identifying the needs analysis. Therefore, this study still needs to be continued, by making teaching materials in the form of modules. After a complete and perfect prototype developed baralah tested validation by experts. From the results of the needs analysis derived from interviews and questionnaires teacher and student questionnaire, can be translated instructional materials Expected load: customs, traditional arts, sites, folklore, heroes, language, events before and after the advent of Islam, the colonial period, period independence and contemporary. Keywords: needs analysis, teaching materials and cultural history of the local content for SD Bone.